Antimicrobial, Antioxidant and Cytotoxic Activities of Glochidion multiloculare (Roxb. ex Willd.) Müll. Arg. (Euphorbiaceae) - Azam, ATM Zafrul; Hasan, Abdullah Al; Uddin, Md Gias; Masud, Mohammad Mehedi; Hasan, Choudhury Mahmood (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The methanol extract (ME) of the powdered bark of Glochidion multiloculare and its six vacuum liquid chromatographic (VLC) fractions (Fa-f) were investigated for antimicrobial, cytotoxic and antioxidant activities. Only fractions Fc and Fd showed mild antimicrobial activity. Significant free radical (DPPH) scavenging activity was found in Ff (IC50 value = 9.27±0.117 ?g/ml). The total phenolic content was measured involving Folin-Ciocalteu reagent and it was the highest in fraction Fe (187.00±1.74 mg of GAE/gm of sample). Cytotoxicity (LC50) by brine shrimp lethality bioassay was found to be significant for Fb (0.023±0.001 ?g/ml), Fc (0.3±0.01 ?g/ml) and Fd (0.117±0.0015 ?g/ml). DOI: http://dx.doi.org/10.3329/dujps.v11i2.14560 Dhaka Univ. J. Pharm. Sci. 11(2): 117-120, 2012 (December)